Host protein CD63 promotes viral RNA replication by interacting with human astrovirus non-structural protein nsP1a/4. (6th February 2019) - Zhao, Wei; Tao, Xiao Li; Liu, Nian; Lu, Heng Zhang; Zheng, Chun Hong; Li, Xiang Yu; Yu, Man; Li, Yong Gang
Abstract : Human astrovirus non-structural protein nsP1a/4, located at the C-terminal end of nsP1a, is thought to be involved in regulating RNA replication. Here, we show that host protein CD63 interacts with the nsP1a protein. Further research showed that the large loop (LEL) domain of CD63 also interacts with nsP1a/4. Confocal microscopy showed that nsP1a/4 protein and CD63 co-localized in the cytoplasm of co-transfected cells. Co-localization of nsP1a/4 and CD63 was also observed in HAstV-1-infected cells. Overexpression of CD63 promoted replication of HAstV-1, whereas knockdown of CD63 reduced production of HAstV-1 viral progeny. These results suggest that CD63 plays a critical role in HAstV-1 replication, and provide an avenue to further understanding the interactions between host and virus proteins during replication and pathogenesis of HAstV.